Descriptions of a new species of Hydroptila Dalman and the mature larva of a species of Stactobiella Martynov from Japan (Trichoptera, Hydroptilidae) - Ito, Tomiko (Zootaxa, 2022)
Description of a new species in the genus Hydroptila Dalman and of the mature larva and case of Stactobiella tshisjakovi (Arefina & Morse 2002) contribute further to studies on the micro-caddisflies of Japan. A single highly distinctive male, Hydroptila hattorii sp. nov. has the dorsal plate flanked by slender lateral arms that bend sharply to meet apically. The larva and case of S. tshisjakovi are similar to those known for congeneric species, but the larva differs from others in the shape of the basal spurs of the tarsal claws and the length of longest seta on the head capsule. The larval habitat in Japan is described.